THEORETICAL ASPECTS OF MODERN ENTREPRENEURSHIP (INTERNATIONAL SCIENTIFIC-ELECTRONIC JOURNAL “PIONEERING STUDIES AND THEORIES”, 2025)
The economic essence of entrepreneurship is considered. The processes taking place in entrepreneurship are investigated. It is noted that modern entrepreneurship is associated with a new management paradigm and the increasing role of innovation. The necessity of rationalization of management through the creation of innovative networks is substantiated. The directions of development of small and medium-sized enterprises are outlined.